Dy Substituted Bifeo3 Nanoparticals: Itsoptical, Structural, Dielectric, Magnetic Properties - Kotha Lakshmana Gupta, Sonali Saha (Mathematical Statistician and Engineering Applications, 2022)
Time-tested materials, such as ferroelectric or magnetic, have led to some of the most significant technical advancements of our day. Off-centre structural distortions and local spins are linked to ferroelectricity and magnetism, respectively. BFO nanoparticles with increased multiferroic characteristics are discussed in this research. Zr4+ doping of BFO nanoparticles has been shown to alter their structural characteristics, resulting in better magnetic and dielectric properties. Structural analysis results demonstrate that Zr4+ doping has a direct impact on the magnetic properties of produced nanoparticles, as well as on the dielectric and optical characteristics.